Quem vai ficar com Laura?: o caso da Galeria Laura Marsiaj no mercado das artes visuais carioca - Pereira, Julia Baker Valls (2016)
The text analyzes one of agents from the art market: the commercial gallery. It was a conscious choice to work with only one gallery and, through this, to understand its microcosms. Beginning with the review of the main authors that work with sociology of art, it was possible to delineate which agents belonged to the field of art and how its relations could happen. The first chapter summarize the theories used through the work, and brings the history of the commercial galleries in Rio de Janeiro. The next two chapters will concentrate in the object of this study: the story of the gallerist Laura Marsiaj and her experiences in the work of art galleries. The construction of these chapters was based in a vast research in newspaper archives, field research and interviews with some important elements from the art’s field that had different connections with Laura. The focus of this dissertation is to create a case study of an art gallery and, through it, see how the relations in the art market occur.